Changed in the Communityâs Livelihood Along Chee River Under The Process of Capitalism: Case Study Chee Wang Kan Village, Mancha Khiri District, khon kaen province. - Putsyainunt, Bodee (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The objective of this article is to understand the general context of the CheeWang Kan village, including of change in Chee Wang Kan livelihood under theprocess of capitalism. This study employed the concept of community economy.In-depth interviews with 10 key informants and 103 household representativeswere applied together with guided questions. The study found that the previouspattern of community economy in Chee Wang Kan village, since 1924, wasagriculture, based on cropped rice for their own consumption and fish from theChee River for their own consumption and for sale. Since 1989, the advance ofagriculture technology meant that they started to use walking tractors on theirfarms. The pattern of the community economy in Chee Wang Kan village changedto be agriculture products for sale. Prior to 2000, area suffered flooding that ledmore laborers in the community to migrate to find work in Bangkok. Consequently,this changed the villagersâ livelihoods, which became a mixture of non-agricultureand agriculture products for sale. This situation continues to the present time.However, the pattern of community economy in Chee Wang Kan village hasadapted to suit the context of the community, having not only agriculture but also anon-agriculture pattern. This has ensured the maintenance of the communityeconomy pattern, under the influence of capitalism, to the present time.Keywords : Community livelihood, Community economy, Capitalism, Chee River, CheeWang Kan